2010
DOI: 10.2118/102100-pa
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Behavior Study of Hydrocarbon/Water/Methanol Mixtures at Reservoir Conditions

Abstract: Summary This paper presents a study of gas/condensate hydrocarbon mixtures and the effect of water, methanol, and isopropanol on their phase behavior. Only sparse data are available on the phase behavior of hydrocarbon/water/methanol mixtures at the high temperatures typical of these reservoirs. Such data are needed for compositional reservoir simulations of well treatments to optimize the performance of solvent treatments of blocked wells. Constant-composition expansion (CCE) experiments were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Binary interaction coefficients and volume shift parameters are modified for the EOS for this kind of calculation. Bang (2005) showed good agreement between experimental data for the hydrocarbon/water and hydrocarbon/water/methanol systems at different temperatures. They modified the binary interaction coefficient and the volume shift parameter for EOS to match the experimental data.…”
Section: Introductionsupporting
confidence: 60%
“…Binary interaction coefficients and volume shift parameters are modified for the EOS for this kind of calculation. Bang (2005) showed good agreement between experimental data for the hydrocarbon/water and hydrocarbon/water/methanol systems at different temperatures. They modified the binary interaction coefficient and the volume shift parameter for EOS to match the experimental data.…”
Section: Introductionsupporting
confidence: 60%
“…Extensive laboratory work was performed by many researchers. The reported experimental studies started at room temperatures (Tang and Firoozabadi 2003), and then were continued by many researchers at higher temperatures of up to 161 C (Fahes and Firoozabadi 2007;Noh and Firoozabadi 2008;Bang et al 2010b). Several fluorinated polymers and surfactants were evaluated.…”
Section: Use Of Fluorosurfactants and -Polymers For Wettability Altermentioning
confidence: 99%
“…Bang et al (2009) found the pressure drop across the core decreased after treating the core samples with fluoropolymer, which indicates that there was an increase in the relative permeability to gas (twofold increase) and the treatment was durable and efficient. In another study, Bang et al (2010b) found that optimal solvents for wettability-alteration chemicals to stimulate the Berea sandstone were the mixture of 2-butoxyethanol and ethanol and the mixture of isopropyl alcohol (IPA) and propylene glycol. Bang et al (2010b) and Wu and Firoozabadi (2010b) found that the water salinity and the type of salt in brine will influence the performance of the fluorochemical and the final change in the wettability of the rock surface.…”
Section: Use Of Fluorosurfactants and -Polymers For Wettability Altermentioning
confidence: 99%
See 1 more Smart Citation
“…Bang et al (2006) measured the gas and oil relative permeabilities over a wide range of capillary numbers. Bang et al (2008) found that condensate buildup in the fractures can significantly reduce the productivity of fractured wells. The steady-state relative permeability in propped fractures is typically on the order of 0.1, which is approximately the same as in the reservoir rock after condensate buildup.…”
Section: Introductionmentioning
confidence: 99%